2015
DOI: 10.1179/1743294415y.0000000069
|View full text |Cite
|
Sign up to set email alerts
|

Pulse electrocodeposition of Ni/MWCNT nanocomposite coatings

Abstract: Nickel/multiwalled carbon nanotube (MWCNT) metal matrix composite coatings were deposited by pulse electrocodeposition method from a Watt's type electrolyte. The influence of peak current density on the particle codeposition and distribution, the surface morphology, microstructure, microhardness and wear resistance of nanocomposite coatings were studied. Copper substrates were used for electrocodeposition and MWCNTs with the diameter of 50-60 nm and length of 10 mm used as reinforcements. The electrodeposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Kartal et al prepared Nickel/MWCNT metal matrix composite coatings by PED method from a Watt's type electrolyte. The resultant coating showed improved microhardness and mechanical behavior [31]. Hatipoglu et al studied Ni/MWCNT nanocomposite coatings from a modified Watt's type electrolyte by using PED technique.…”
Section: Introductionmentioning
confidence: 99%
“…Kartal et al prepared Nickel/MWCNT metal matrix composite coatings by PED method from a Watt's type electrolyte. The resultant coating showed improved microhardness and mechanical behavior [31]. Hatipoglu et al studied Ni/MWCNT nanocomposite coatings from a modified Watt's type electrolyte by using PED technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that electroplating by using pulse current technique results in the production of deposits with improved mechanical properties and with more uniformly distributed metal ions, in comparison with direct current technique [11][12][13][14]. Some important equations used in pulse electrodeposition are as follows [11]:…”
Section: Introductionmentioning
confidence: 99%
“…Electroless plating is one of the most popular technology, which has been widely used as an effective way for surface-modification of CNTs because that it is much simpler, lower cost and without vacuum or high temperature. 1-6 The metallic ions change into metal and deposit on the substrate surface to form surface modified coating through the chemical reduction. 7-9 At present, most research activities have been focused on electroless Ni, Fe and alloy plating on CNTs, 10-14 and only limited research has been concerned with plating Co and Co–P alloy.…”
Section: Introductionmentioning
confidence: 99%